Parafoveal processing in word recognition. - Kennedy, Alan (Quarterly Journal of Experimental Psychology: Section A, 2000)
A study was conducted to examine parafoveal processing in word recognition. Data were gathered from two experiments conducted on two samples of 20 students. The results support the proposition that foveal and parafoveal processing occurs in parallel, with processing distributed over a region greater than a single word. The findings suggest little influence of any of the manipulated variables on saccade extent.